Maintaining order on stage :|criminalizing performing arts in Late Ottoman Istanbul (1878 - 1908) - Özözer, Defne. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis examines the Ottoman State’s criminal approach towards performing arts in Istanbul between 1878 and 1908. The main goal is to understand and analyze the reasons for criminalization. Exploring the different patterns of intervention developed over the years, this thesis aims to apprehend how social order is exercised in performing arts at the turn of the 19th century in Ottoman Istanbul. The study tries to situate the cases of performance criminalization in the larger political context and displays the state’s attitude towards entertainment and its control over the social order. The primary sources used in the thesis provide a map of main entertainment sites and a repertoire of genres in Beyoğlu and Kadıköy neighborhoods. Therefore, the study offers a new methodological venue in researching the history of performing arts in urban areas of 19th century Ottoman Istanbul. Ottoman performances have been a domain thoroughly researched from different perspectives. The basis of this research primarily consists of documents from the Ottoman State Archives, which report interventions in performance-related sites like theaters, coffeehouses, and other urban gathering spaces, including winehouses or beerhouses. The narratives of these primary sources present a historical ethnography of the sites, performers, and performances of the late Ottoman scene of performing arts. They also show how criminalization generates a research tool for social historians.
Keywords: Criminal act -- Turkey.; Performing arts -- Turkey -- History